Praktik Mappaje Perspektif Fikih Muamalah (Studi Kasus di Desa Tolowe Ponre Waru, Kec. Wolo, Kab. Kolaka) - Mudabbir, Ahmad; Abdul Hayyaqdhan Ashufah; Muhammad Najib (Fakultas Syariah IAIN Kendari, 2026)
The study aims to determine the implementation of mappaje practices in Tolowe Ponre Waru Village, Wolo District, Kolaka Regency, and analyze the practices based on the perspective of muamalah fiqh in Islamic economic law. This study explores the practice of mappaje from a jurisprudence-based perspective. The primary focus of this research is to understand how this practice is carried out, its underlying values, and its alignment with the principles of jurisprudence-based principles. This study uses a qualitative research method with an empirical approach. Data collection techniques are carried out through observation, interviews, and documentation of mappaje actors, community leaders, and local religious leaders. The data obtained were analyzed descriptively qualitatively by linking field facts and muamalah fiqh provisions. The results show that mappaje practices in Tolowe Ponre Waru Village is carried out through several stages, namely initial offers and communication, inspection and assessment of plant conditions, and implementation of a verbal sale and purchase agreement based on an agreement between both parties. This practice is carried out of mutual consent and has become a local custom. From the perspective of Islamic jurisprudence (fiqh) of muamalah (contractual transactions), mappaje is essentially permissible as long as it meets the pillars and conditions of a sale and purchase, does not involve any element of fraud, and minimizes the element of gharar through clarity of agreement and honesty between the parties. Therefore, mappaje is acceptable under Islamic economic law if implemented in accordance with the principles of justice, benefit, and prudence. Keywords: Fiqh of Muamalah; Gharar; Mappaje, Sale and Purchase.